Ozonation enables to suppress horizontal transfer of antibiotic resistance genes in microbial communities during swine manure composting - Fu, Qiqi; Chen, Zhiqiang; Yu, Zhigang; Wu, Yiqi; Bao, Huanyu; Guo, Jianhua; Wen, Qinxue (Chemical engineering journal (Lausanne, Switzerland : 1996), 2023)
[Display omitted] •Contribution of intra- and extracellular ARGs to their rebounding was distinguished.•Extracellular ARGs were more persistent than most targeted intracellular ARGs.•Microbes’ transformation frequencies kept high disregarding low MGEs abundance.•HGT possibility may be underestimated by only considering MGEs profile.•Ozone assistant treatment was optimized to significantly reduce HGT possibility. Although aerobic composting process has been proposed as an efficient approach to treat livestock manure, the evolution patterns of extracellular antibiotic resistance genes (eARGs) and intracellular antibiotic resistance genes (iARGs) and their horizontal transfer during composting are unclear. Here, the variations of iARGs and eARGs during swine manure composting were systematically analyzed. We found that the abundance of ARGs rebounded from thermophilic phase to mature phase. This was due to the release of persistent eARGs and the increase of certain iARGs during cell proliferation. The conjugative transfer frequencies of ARGs in composting communities were (1.68 ± 0.2) × 10-1 Transconjugant/Donor + Recipient (TC/D + R) in composting products, which was comparable to the frequency before the composting. Ozone was then optimized to suppress the rebound and spread of ARGs. We found that the low ozone dosage of 0.4 g/kg FW in the cooling phase could not only significantly remove iARGs (2.02-logs less than the control, 8 of 12 targeted iARGs were not detected) by eliminating the potential hosts, but also decrease the possibilities of both conjugation and transformation among the composting products by eliminating both HGT (conjugation and transformation) efficiencies of microbes and microbes themselves. Collectively, this study proposes the optimal ozonation strategy to mitigate the dissemination of ARGs in the composting products.